Combining photogrammetry and augmented reality towards an integrated facility management system for the oil industry - Hou, Lei; Wang, Ying; Wang, Xiangyu; Maynard, Nicoleta; Cameron, I.; Zhang, S.; Jiao, Y. (IEEE, 2014)
The capabilities of applying smart information management systems for facility management (FM) in oil refining context have not yet been fully exploited. This paper presents a study that investigates the applicability of integrating advanced technologies such as augmented virtuality (AV), augmented reality (AR), and server-sustained information modeling (IM) in facilitating FM activities for a petroleum refinery. The paper starts with a thorough review on previouswork in which multiple information processing technologies are applied to aid FM. The following section presents the conceivable merits when the novel visualization is formulatedto enhance the conventional IM application. It then proposes a novel system framework based on technological feasibility and further describes the development of a system prototype thatboosts immersive and interactive experiences to FM toward a multitude of electrical components. It is noted that this paper focuses on the method for the technological realization of thesystem. With the successful development of the system, it is able to deal with the management of complex information flows, support the users’ navigation in geo-coordinates, andenables a succinct smart IM interface with switchable AV/AR scenes. In view that IM has been proved suitable in supporting real-time communication and information management whileAV/AR can be effectively used to improve the way how information is exhibited into real workspaces, the system proves the concept of IM+AV/AR in the context of FM in arefinery. Future work will be conducted on the evaluation of system effectiveness and system optimization, with the aim of functional improvement and performing a feasibility study.